Two-Dimensional Steady Flow Modeling of Ideal Fluid in Porous Medium Using Finite Element Method - Hairil Anwar; Wahyu Srigutomo (Indonesian Journal of Physics, 2015)
Ideal fluid is a fluid which is uncompressed and has no viscosity. A steady stream of ideal fluid in a porous medium can be modeled using finite element method. The finite element method is a numerical method that can be used to solve boundary-value problem governed by a differential equation and a set of boundary conditions. In this modeling, the linear system of equations derived using Galerkin approach for linear triangular elements. Irregular geometry and variation in permeability distribution models are used. The solution obtained in form of fluid head and fluid flow velocity distribution in the modeling domain.